PRACTICAL STATUS OF THE STUDY OF FRENCH LANGUAGE AND CULTURE IN PEDAGOGICAL HIGHER EDUCATION INSTITUTIONS (Conference Zone, 2022)
Whether students retain their native language successfully when acquiring additional languages depends on factors affecting one another. Studies have shown that language education is needed from six to eight years to develop the level of literacy and verbal pronunciation necessary for academic achievement in secondary school. In addition, the prohibitions define that fluency and literacy in their native language create a cognitive and linguistic basis for the study of additional languages. And this serves as an important basis in the study of other foreign languages. In this article, opinions and comments are made on the practical status of the study of the French language and culture in pedagogical higher education institutions